Beginning Linux Programming, Third Edition - Stones, Richard (Wiley Publishing, 2011)
f you have some programming experience and are ready to venture into Linux programming, this updated edition of the bestselling entry-level book takes you there. The authors guide you step by step, using construction of a CD database application to give you hands-on experience as you progress from the basic to the complex. You’ll start with fundamental concepts like writing Unix programs in C. You’ll learn basic system calls, file I/O, interprocess communication, and shell programming. You’ll become skilled with the toolkits and libraries for working with user interfaces.